Caring Perawat Mempengaruhi Kepuasan Pasien di Instalasi Rawat Inap - Nursanti Christianingsih; Mohammad Heri Kurniawan; Mega Hasanul Huda; Ening Wahyuni (Akademi Keperawatan Hermina Manggala Husada, 2022)
Nurse caring behavior is the core or focus in nursing as a form of professional nursing practice and caring behavior is an indicator of patient satisfaction. The purpose of this study was to determine the relationship of nurse caring to the level of patient satisfaction in the inpatient room at Hermina Galaxy Hospital. This study uses quantitative methods. The sampling technique used purposive sampling technique with a sample of 50 respondents who were in accordance with the inclusion and exclusion criteria. The results showed that 32 respondents said caring nurses were good, 19 respondents were satisfied and 13 respondents were dissatisfied. Of the 18 respondents who said that nurse caring was lacking, 7 respondents were satisfied and 11 respondents were dissatisfied. Correlation test results obtained an r value of 0.494 and a p value of 0.000, the conclusion of these results is that the relationship between nurse caring and patient satisfaction shows a positive relationship and has a positive pattern, meaning that the higher the nurse's caring, the higher the level of patient satisfaction. There is a relationship between nurse caring and patient satisfaction in the inpatient room at Hermina Galaxy Hospital.